National and regional prevalence of SARS-CoV-2 antibodies in primary and secondary school children in England: the School Infection Survey, a national open cohort study, November 2021SARS-CoV-2 antibody prevalence in school children. Issue 4 (April 2023) - Powell, Annabel A.; Ireland, Georgina; Leeson, Rebecca; Lacey, Andrea; Ford, Ben; Poh, John; Ijaz, Samreen; Shute, Justin; Cherepanov, Peter; Tedder, Richard; Bottomley, Christian; Dawe, Fiona; et al.
Summary: Background: SARS-CoV-2 infection rates are likely to be underestimated in children because of asymptomatic or mild infections. We aim to estimate national and regional prevalence of SARS-CoV-2 antibodies in primary (4–11 years old) and secondary (11–18 years old) school children between 10 November and 10 December 2021. Methods: Cross-sectional surveillance in England using two-stage sampling, firstly stratifying into regions and selecting local authorities, then selecting schools according to a stratified sample within selected local authorities. Participants were sampled using a novel oral fluid-validated assay for SARS-CoV-2 spike and nucleocapsid IgG antibodies. Results: 4980 students from 117 state-funded schools (2706 from 83 primary schools, 2274 from 34 secondary schools) provided a valid sample. After weighting for age, sex, and ethnicity, and adjusting for assay accuracy, the national prevalence of SARS-CoV-2 antibodies in primary school students, who were all unvaccinated, was 40.1% (95% CI 37.3–43.0). Antibody prevalence increased with age (p < 0.001) and was higher in urban than rural schools (p = 0.01). In secondary school students, the adjusted, weighted national prevalence of SARS-CoV-2 antibodies was 82.4% (95% CI 79.5–85.1); including 71.5% (95% CI 65.7–76.8) in unvaccinated and 97.5% (95% CI 96.1–98.5) in vaccinated students. Antibody prevalence increased with age (p < 0.001), and was not significantly different in urban versus rural students (p = 0.1). Conclusions: In November 2021, using a validated oral fluid assay, national SARS-CoV-2 seroprevalence was estimated to be 40.1% in primary school students and 82.4% in secondary school students. In unvaccinated children, this was approximately threefold higher than confirmed infections highlighting the importance of seroprevalence studies to estimate prior exposure. Data availability: Deidentified study data are available for access by accredited researchers in the ONS Secure Research Service (SRS) for accredited research purposes under part 5, chapter 5 of the Digital Economy Act 2017. For further information about accreditation, contact Research.support@ons.gov.uk or visit the SRS website.